Pengaruh Jenis Finir Dan Jumlah Perekat Terhadap Kualitas Plywood Interior : Effect of Veneer Type and Amount of Adhesive on Plywood Face Coating - Nurmadina, Nurmadina; Wijayanto, Arip; Widiyanto, Wahyu; Nugroho, Alfani Risman; Purwanto, Agung Ari (Jurnal Silva Tropika, 2022)
Utilization of composite boards for furniture has been widely used in order to substitute solid wood. Coating veneer (veneering) is a technique to improve the appearance of composite panel products, such as plywood. This research was conducted to determine the effect of the type of veneer and the mass of adhesive lath on the physical and mechanical properties of veneering plywood. The veneer used are from teak, mahogany and mindi. The adhesive used was polyvinyl acetate (PVAc) with a melting weight of 130 g/m2, 150 g/m2, 170 g/m2. The results showed that the type of veneer had no effect on the physical and mechanical properties of the composite board. The physical properties in the form of density are affected by the weight of the adhesive, the higher the amount of adhesive, the higher the density. Veneer delamination with glue spread of 150 and 170 g/m2 complies with JAS Type 2 standards. Veneer composite products with PVAc adhesives can be used in interior areas where there is frequent short term exposure to water.   Keywords: adhesive, glue spread, plywood, veneer   ABSTRAK Pemanfaatan plywood untuk furnitur telah banyak digunakan dalam rangka mensubtitusi kayu pejal. Veneering merupakan suatu teknik pelapisan permukaan untuk meningkatkan penampilan panel misalnya pada plywood. Penelitian ini dilakukan untuk mengetahui pengaruh jenis finir dan berat labur perekat terhadap sifat fisika dan mekanika veneering plywood. Finir yang digunakan adalah dari kayu jati, mahoni dan mindi. Perekat yang digunakan adalah polyvinyl asetat (PVAc) dengan berat labur 130 g/m2, 150 g/m2, 170 g/m2 . Hasil penelitian menunjukkan jenis finir tidak berpengaruh terhadap sifat fisika, mekanika papan komposit. Sifat kerapatan dipengaruhi oleh berat labur perekat, yaitu semakin tinggi berat labur maka kerapatan semakin meningkat. Delaminasi veneering dengan berat labur 150 dan 170 g/m2 memenuhi standar JAS Type 2. Produk komposit veneering dengan perekat PVAc dapat digunakan pada interior dan dapat perpapar kelembapan secara singkat.   Katakunci: berat labur, finir, perekat, plywood